The effect of nuclear transcriptional factor κВ activation inhibitor – curcumine on the experimental immune liver disease - I. N. Alekseyeva; N. V. Makogon; S. I. Pavlovich; T. M. Bryzgina; L. I. Aleksyuk; T. V. Martynova; V. S. Sukhina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study at two models of immune hepatitis (Т-cellular and antibody origin) in mice damage of the liver, activity and destruction of its immunocompetent cells, thymus gland and the spleen, as well as the effect of curcumine — inhibitor of NF-κB activation on development of pathological process.Material and methods. An immune lesion of the liver in mice of СВА line was invoked by Т-cellular mitogen concanavalin A and xenogenic anti-liver antibodies. Study was carried out with application of histological, cytological and biochemical methods.Results. In comparative studies features of hepatitis development of cellular and antibody origin were revealed. At Т-cellular hepatitis cytolytic component of liver lesion, primary and secondary cell necrosis, depression of cytophagous activity of macrophages that causes preconditions for enhancement of inflammation were more intensive. At hepatitis of antibody origin, at least at early stages, vascular and immunological reactions are expressed in the liver.Conclusion. Curcumine, the inhibitor of NF-κB activation reduces preconditions for development of inflammatory response at experimental Т-cellular hepatitis, and has protective action for the liver.